Finding rhythms made me find my rhythm in prison”: the role of a music program in promoting social engagement and psychological well-being among inmates - Kyprianides, Arabella (The prison journal, 2020)
This article presents a mixed-methods evaluation of the Finding Rhythms (FR) charity music program in U.K. prisons. Results across two studies indicate that FR group activities and the development of a shared FR identity lead to a positive well-being outcome. Furthermore, FR involvement dissolves rivalries between prisoners and provides them with a sense of purpose that extends into prison life and beyond. We provide evidence for the social cure properties of the FR group and the music program that promotes social engagement and psychological well-being among inmates.